2012
DOI: 10.1007/s10578-012-0323-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Prefrontal Hemodynamic Response in Pediatric Obsessive–Compulsive Disorder as Measured by Near-Infrared Spectroscopy

Abstract: Recent developments in near-infrared spectroscopy (NIRS) have enabled non-invasive clarification of brain functions in psychiatric disorders. Functional neuroimaging studies of patients with obsessive-compulsive disorder (OCD) have suggested that the frontal cortex and subcortical structures may play a role in the pathophysiology of the disorder. Twelve treatment-naïve children with OCD and 12 age- and sex-matched healthy control subjects participated in the present study after giving consent. The relative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…Ota et al8 reported a smaller response in the frontopolar region in the pediatric OCD group, while Okada et al9 reported a smaller response in the left lateral prefrontal region in adult patients with OCD. In the present study, adult patients with OCD had significantly smaller changes in oxygenated hemoglobin concentrations than controls at channel 18, localized near the right lateral prefrontal region.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ota et al8 reported a smaller response in the frontopolar region in the pediatric OCD group, while Okada et al9 reported a smaller response in the left lateral prefrontal region in adult patients with OCD. In the present study, adult patients with OCD had significantly smaller changes in oxygenated hemoglobin concentrations than controls at channel 18, localized near the right lateral prefrontal region.…”
Section: Discussionmentioning
confidence: 98%
“…In an NIRS study, Ota et al8 and Okada et al9 showed that prefrontal hemodynamic responses were lower in both adult and pediatric patients with OCD using the Stroop color-word task, but that the areas with a reduced prefrontal hemodynamic response were different between these two populations. Ota et al8 reported a smaller response in the frontopolar region in the pediatric OCD group, while Okada et al9 reported a smaller response in the left lateral prefrontal region in adult patients with OCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intellectual level was assessed using the Wechsler intelligence scale for children-fourth edition (WISC-IV), and individuals with full-scale IQ (FIQ) scores below 70 were excluded. We also excluded those who presented with a comorbid Axis I diagnosis, a neurological disorder, a head injury, a serious medical condition, or a history of substance abuse/dependence because these influenced the prefrontal hemodynamic response [2022, 24, 26, 35, 36]. In total, 30 participants with ADHD who had no previous medication history were enrolled in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Nearinfrared spectroscopy: NIRS Fukuda, 2012NIRS Hirosawa et al, 2013Nakanishi et al, 2014;Okada et al, 2013;Ota et al, 2013;Takeda et al, 2017 Table 1 16…”
Section: Nirsmentioning
confidence: 99%